HISTORIA KARDIO- I TORAKOCHIRURGIIPressure chamber or intubation? The beginnings of thoracic surgery at the turn of the nineteenth and twentieth centuries - Gryglewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
The origins of the thoracic surgery date back to the turn nineteenth and early twentieth century. The main, although not the only, reason for which operations on the open chest was thought to be impossible lied in pneumothorax. Suitable conditions to overcome this problem appeared in the nineteenth century. This were: the rise of the methods of anesthesia, asepsis and antisepsis, and finally use in physiological experiments method of intubation. Undesirable subsidence in the lungs can be eliminated by supplying air thereto at elevated pressure or by lowering the external pressure in a special chamber. The first solution was associated primarily with the development of intubation methods. The second was based on the construction of special chambers. Overpressure and underpressure were in the early twentieth century, regarded as equivalent, and both were to play a key role in the birth of modern thoracic surgery.